Mesenchymal stem cell-derived extracellular vesicles, osteoimmunology and orthopedic diseases - Ma,Maoxiao; Cui,Guofeng; Liu,Youwen; Tang,Yanfeng; Lu,Xiaoshuai; Yue,Chen; Zhang,Xue (PeerJ, 2023)
Mesenchymal stem cells (MSCs) play an important role in tissue healing and regenerative medicine due to their self-renewal and multi-directional differentiation properties. MSCs exert their therapeutic effects mainly via the paracrine pathway, which involves the secretion of extracellular vesicles (EVs). EVs have a high drug loading capacity and can transport various molecules, such as proteins, nucleic acids, and lipids, that can modify the course of diverse diseases. Due to their ability to maintain the therapeutic effects of their parent cells, MSC-derived EVs have emerged as a promising, safe cell-free treatment approach for tissue regeneration. With advances in inflammation research and emergence of the field of osteoimmunology, evidence has accumulated pointing to the role of inflammatory and osteoimmunological processes in the occurrence and progression of orthopedic diseases. Several studies have shown that MSC-derived EVs participate in bone regeneration and the pathophysiology of orthopedic diseases by regulating the inflammatory environment, enhancing angiogenesis, and promoting the differentiation and proliferation of osteoblasts and osteoclasts. In this review, we summarize recent advances in the application and functions of MSC-derived EVs as potential therapies against orthopedic diseases, including osteoarthritis, intervertebral disc degeneration, osteoporosis and osteonecrosis.
Keywords: Mesenchymal stem cell; Extracellular vesicles; Osteoimmunology; Orthopedic diseases